2015
DOI: 10.12998/wjcc.v3.i9.757
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and hepatocellular carcinoma: The basic and clinic

Abstract: Vitamin K (VK), which was originally identified as a cofactor involved in the production of functional coagulation factors in the liver, has been shown to be involved in various aspects of physiological and pathological events, including bone metabolism, cardiovascular diseases and tumor biology. The mechanisms and roles of VK are gradually becoming clear. Several novel enzymes involved in the VK cycle were identified and have been shown to be linked to tumorigenesis. The VKs have been shown to suppress liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 96 publications
0
26
0
1
Order By: Relevance
“…Therefore, DCP stimulates HCC cell proliferation through the DCP‐Met‐JAK‐STAT3 signaling pathway . It is well known that VK treatment suppresses increases in serum DCP levels . In this case, the patient's DCP level has significantly reduced after treatment with VK2 analog.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Therefore, DCP stimulates HCC cell proliferation through the DCP‐Met‐JAK‐STAT3 signaling pathway . It is well known that VK treatment suppresses increases in serum DCP levels . In this case, the patient's DCP level has significantly reduced after treatment with VK2 analog.…”
Section: Discussionmentioning
confidence: 94%
“…Vitamin K has been reported to show an antitumor effect in several cancer types, including HCC . In clinical practice, there have been some reports that a VK2 analog is beneficial for the prevention of recurrence in HCC patients after curative therapy, although this effect was not confirmed in a large‐scale randomized controlled trial . However, meta‐analyses have shown that VK2 analog administration might reduce the rate of recurrence after 1 year, and improve overall survival in HCC patients as early as 1 year .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, many reports have shown that MK-4 has antioncogenic effects within various cancer cell lines, including leukemia, lung cancer, ovarian cancer, prostate cancer, and hepatocellular carcinoma (HCC) [3][4][5][6]. Specifically, numerous articles describe the effects of MK-4 against HCC.…”
Section: Introductionmentioning
confidence: 99%